2010
DOI: 10.1371/journal.pone.0009097
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Characterization of Recombinant Hemagglutinin Proteins Derived from Different Avian Influenza Virus Subtypes

Abstract: Since the advent of highly pathogenic variants of avian influenza virus (HPAIV), the main focus of avian influenza research has been the characterization and detection of HPAIV hemagglutinin (HA) from H5 and H7 subtypes. However, due to the high mutation and reassortation rate of influenza viruses, in theory any influenza strain may acquire increased pathogenicity irrespective of its subtype. A comprehensive antigenic characterization of influenza viruses encompassing all 16 HA and 9 neuraminidase subtypes wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…In poultry, activity of cross-reactive CD8+ cytotoxic T cells induced by a H9N2 infection have been shown to cause protection to later HPAI H5N1 challenges [34], [40]. Some studies have reported highly conserved inter-subtype immunodominant epitopes that could explain cross-reactivity [41]. Similarly, the “broadly neutralizing antibodies” observed in humans and mice confer cross-reactive activity and neutralize multiple IAVs subtypes from Group 1 and 2 [42], [43].…”
Section: Discussionmentioning
confidence: 99%
“…In poultry, activity of cross-reactive CD8+ cytotoxic T cells induced by a H9N2 infection have been shown to cause protection to later HPAI H5N1 challenges [34], [40]. Some studies have reported highly conserved inter-subtype immunodominant epitopes that could explain cross-reactivity [41]. Similarly, the “broadly neutralizing antibodies” observed in humans and mice confer cross-reactive activity and neutralize multiple IAVs subtypes from Group 1 and 2 [42], [43].…”
Section: Discussionmentioning
confidence: 99%
“…The deduced amino acid sequences of challenge virus HA gene (accession number is EPI954663 in GISAID EpiFlu database) and the rHVT-H5 vaccine insert (accession number is KP969039 in GenBank) were aligned and pairwise comparison was prepared in CLC Main Workbench 7.9.1. Predicted H5 epitopes were annotated based on the identified epitopes by using polyclonal rabbit antisera for epitope scanning of baculovirus-expressed H5 HA protein [23]. Further antigenicity-associated sites [24, 25], predicted MHC antigenic sites [25, 26], and the previously identified MHCI/II peptide [27] were also compared between the vaccine and the challenge virus.…”
Section: Methodsmentioning
confidence: 99%
“…In order to quantify H5-specific IgY titers by ELISA [59], 96-well immunoplates (Maxisorb, Nunc) were coated with purified baculovirus-derived recombinant influenza H5 protein (100 ng/100 µl per well, a kind gift from Dr. Matthias Müller, IVI, Switzerland) in 50 mM bi-carbonate buffer pH 9.6 overnight at 4°C. The plates were then blocked with 200 µl/well PBS containing 0.2 M NaCl and 10% defatted dry milk at 37°C for 1 h. The wells were washed three times with 300 µl of wash buffer (PBS containing 0.01% Tween-20).…”
Section: Methodsmentioning
confidence: 99%